Cognitive-pragmatic potential of substitutes in digital communication: anthroponymic aspect - A. Bocharova (Ибероамериканские тетради)
The article deals with the investigation of the cognitive-pragmatic potential of substitutes in the Internet space as a new platform of language. As a research material we used the content of the forums of electronic periodicals, because of the fact that nowadays the forum has transformed to an important information-communication block, which reflect a special cluster of psychophysiological properties and essential qualities of the modern society. The forumers use a wide range of linguistic means and the lexical substitutes become one of the symbol-forming elements.